Kinetic model for carbon species distribution in arc discharge plasma - Roslan, M. S.; Chaudhary, K.; Aziz, M. S.; Ali, J.; Yupapin, P. P.; Bidin, N.; Saktioto (My University, 2015)
In present work, numerical integration for density distribution of carbon species in arc discharge plasma is presented. The model incorporates two-body collision effects using continuity equation of density in conservation mass rate law. Plasma species in inter-electrode gap are accelerated by the electric field across the gap and produced high density plasma. Electrons with high energy in arc discharge plasma cause extended ionization, excitation, recombination, and dissociation process due to particle collision which leads to enrichment of density in spatial and temporal mode. The extrapolation of species dominant in arc discharge process is critical issue to predict carbon nanostructure production. A chemical kinetic models and distribution of carbon ions and neutrals species based on collision in thermal plasma condition is developed. The reaction process of carbon species are identified in the between electrodes region. The electron-ion recombination cross section is analyzed to understand the density evolution.
Keywords: Arc discharge plasma; Carbon ion species; Chemical kinetic model